2022
DOI: 10.3390/nu14224862
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Choline Intake in Pregnant Women in Germany

Abstract: Choline is an essential nutrient that is involved in various developmental processes during pregnancy. While the general adequate choline intake (AI) for adults has been set at 400 mg/day by the European Food Safety Authority (EFSA), an AI of 480 mg/day has been derived for pregnant women. To date, the choline intake of pregnant women in Germany has not been investigated yet. Therefore, in this survey, the total choline intake from dietary and supplementary sources in pregnant women was estimated using an onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The current reference intakes for choline for pregnant and lactating women (450 and 550 mg/d according to NAM) [ 1 , 3 ] are likely to be sufficient for normal fetal development in uncomplicated pregnancies. However, the majority of young women consume approximately 300 mg/d of choline, which is 150–250 mg/d lower than the reference intake values [ 81 , 82 ]. Therefore, public health policies are needed to ensure sufficient choline intake through adding choline to maternal multivitamin supplements.…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…The current reference intakes for choline for pregnant and lactating women (450 and 550 mg/d according to NAM) [ 1 , 3 ] are likely to be sufficient for normal fetal development in uncomplicated pregnancies. However, the majority of young women consume approximately 300 mg/d of choline, which is 150–250 mg/d lower than the reference intake values [ 81 , 82 ]. Therefore, public health policies are needed to ensure sufficient choline intake through adding choline to maternal multivitamin supplements.…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…Those following vegetarian or vegan diets, which typically exclude animal products high in choline, may be particularly at risk. With careful planning and including plant-based sources of choline, individuals on these diets may be able to meet their choline requirements, potentially putting both maternal and fetal health at risk [ 12 ].…”
Section: Reviewmentioning
confidence: 99%
“…Research has indicated that many pregnant women do not meet the recommended choline intake levels. The prevalence of deficiency can vary by region, dietary habits, and population demographics [ 12 ]. To address this concern, it is essential to assess the dietary habits of pregnant women and understand the factors contributing to choline deficiency.…”
Section: Reviewmentioning
confidence: 99%
“…Average choline intakes amongst women of childbearing age have been explored in a review of 23 studies, and were reported to range from 233 mg/day to 383 mg/day, even with the inclusion of choline from supplements, and thus are consistently lower than the estimated adequate intake (AI) of 480 mg/day for pregnant women [ 45 , 46 ]. In a recent study conducted in Germany, only 7% of pregnant women achieved adequate choline intakes [ 47 ]. Similarly, amongst an Australian sample of pregnant women, median choline intake was 362 mg/day in early pregnancy, with eggs providing around 17% of the choline [ 48 ].…”
Section: In Utero Originsmentioning
confidence: 99%